A pooled analysis of temporal trends in the prevalence of anxiety-induced sleep loss among adolescents aged 12–15 years across 29 countries - Xu, Guodong; Li, Lian; Yi, Lijuan; Li, Tao; Chai, Qiongxia; Zhu, Junyang (Frontiers in Psychiatry, 2023)
Background: Previous studies examining trends in sleep loss among adolescents have mainly focused on single countriy and region. This study aims to analyze temporal trends in the prevalence of anxiety-induced sleep loss among adolescents from 29 countries in five regions. Methods: This study used data from the Global School-based Student Health Survey 2003-2018, which surveyed 215,380 adolescents from 29 countries with at least two cross-sectional surveys per country. The weighted country-specific prevalence of anxiety-induced sleep loss and trends across the survey years were evaluated. Randomor fixed-effects meta-analyses were used to calculate pooled prevalence and temporal trends across 29 countries.Results: Temporal variations in anxiety-induced sleep loss across countries were identified. Increasing (Suriname, Vanuatu, and Myanmar), decreasing (Namibia, Jamaica, the Philippines, Samoa, and Indonesia), and stable (all other countries) trends in anxiety-induced sleep loss were noted. The pooled weighted prevalence of anxietyinduced sleep loss was 11.35% and 10.67% in the first and last surveys, respectively.There was no meaningful change in the propensity to have anxiety-related sleep disorders over time, with the reduction and OR of these two surveys being 0.54 (-0.53-1.61) and 0.98 (0.88-1.10). For subgroup analyses, no significant differences in pooled anxiety-induced sleep loss trends were seen between the two surveys for different sexes, regions, incomes, survey years in the first wave, survey periods, or number of surveys.Trends in the prevalence of anxiety-induced sleep loss in adolescents varied significantly across different countries. Generally, a stable trend was observed in 21 of the 29 countries surveyed. Our study provides data that can aid policymakers in establishing country-specific strategies for reducing anxiety-induced sleep loss in adolescents.